Functional Foods and Nutraceuticals in the Primary Prevention of Cardiovascular Diseases - Eman M. Alissa; Gordon A. Ferns (Journal of Nutrition and Metabolism)
Cardiovascular disease (CVD) is now the leading cause of death globally and is a growing health concern. Dietary factors are important in the pathogenesis of CVD and may to a large degree determine CVD risk, but have been less extensively investigated. Functional foods are those that are thought to have physiological benefits and/or reduce the risk of chronic disease beyond their basic nutritional functions. The food industry has started to market products labelled as “functional foods.” Although many review articles have focused on individual dietary variables as determinants of CVD that can be modified to reduce the risk of CVD, the aim of this current paper was to examine the impact of functional foods in relation to the development and progression of CVD. Epidemiologic studies have demonstrated the association between certain dietary patterns and cardiovascular health. Research into the cardio-protective potential of their dietary components might support the development of functional foods and nutraceuticals. This paper will also compare the effect of individual bioactive dietary compounds with the effect of some dietary patterns in terms of their cardiovascular protection.